Opposite of always - Reynolds, Justin A. (Katherine Tegen Books, an imprint of HarperCollinsPublishers, 2019)
After falling for Kate, her unexpected death sends Jack back in time to the moment they first met. He soon learns that his actions have consequences when someone else close to him dies.